Estrategias metodológicas y su aporte en el aprendizaje en los estudiantes del tercer semestre de la Carrera de Turismo periodo abril - septiembre 2022 - Carvajal Avendaño, Carlos Andres (2022)
In the present research project, it provides truthful and reliable information about the current situation in which the students of the third semester of the tourism career of the Technical University of Babahoyo find themselves, in the learning they have when receiving their classes according to the methodological strategies implemented by their teachers in the current academic period April-September 2022. Methodological strategies in a general way are very necessary for the increase of cognitive skills, which allows them to acquire important learning knowledge, also helps to reveal the deficiencies and possible unfavorable situations that teachers can commit in the application of their classes. The objective of the current study; is to know the contribution that the methodological strategies have in the learning of the students of the third semester of the tourism career in the period April-September 2022, for this, didactic methods were used, covering descriptive research with a type of exploratory design. In addition, the research was carried out through a field study in which the elaboration of a questionnaire was implemented as an instrument to carry out a survey of all the students of said career, thus allowing to determine that; the teachers of the third semester of the tourism career do not use all the methodological strategies to teach their classes.